Clinical, polysomnographic and genome‐wide association analyses of narcolepsy with cataplexy: a European Narcolepsy Network study. (18th March 2013) - Luca, Gianina; Haba‐Rubio, José; Dauvilliers, Yves; Lammers, Gert‐Jan; Overeem, Sebastiaan; Donjacour, Claire E.; Mayer, Geert; Javidi, Sirous; Iranzo, Alex; Santamaria, Joan; Peraita‐Adrados, Rosa; Hor, Hyun; et al.
Summary The aim of this study was to describe the clinical and PSG characteristics of narcolepsy with cataplexy and their genetic predisposition by using the retrospective patient database of the European Narcolepsy Network (EU‐NN). We have analysed retrospective data of 1099 patients with narcolepsy diagnosed according to International Classification of Sleep Disorders‐2. Demographic and clinical characteristics, polysomnography and multiple sleep latency test data, hypocretin‐1 levels, and genome‐wide genotypes were available. We found a significantly lower age at sleepiness onset (men versus women: 23.74 ± 12.43 versus 21.49 ± 11.83, P = 0.003) and longer diagnostic delay in women (men versus women: 13.82 ± 13.79 versus 15.62 ± 14.94, P = 0.044). The mean diagnostic delay was 14.63 ± 14.31 years, and longer delay was associated with higher body mass index. The best predictors of short diagnostic delay were young age at diagnosis, cataplexy as the first symptom and higher frequency of cataplexy attacks. The mean multiple sleep latency negatively correlated with Epworth Sleepiness Scale (ESS) and with the number of sleep‐onset rapid eye movement periods (SOREMPs), but none of the polysomnographic variables was associated with subjective or objective measures of sleepiness. Variant rs2859998 in UBXN2B gene showed a strong association (P = 1.28E‐07) with the age at onset of excessive daytime sleepiness, and rs12425451 near the transcription factor TEAD4 (P = 1.97E‐07) with the age at onset of cataplexy. Altogether, our results indicate that the diagnostic delay remains extremely long, age and gender substantially affect symptoms, and that a genetic predisposition affects the age at onset of symptoms.